Efektivitas Metode Semantik Divergen Terhadap Kemampuan Bahasa Ekspresif Pada Penderita Afasia Lancar Di Kecamatan Jebres - Hinggil Novalia Naluri Tasari; Muryanti Muryanti (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Abstract Background: Aphasia is a language disorder that causes sufferers to be unable or even completely unable to speak normally anymore. Aphasia consists of 2 categories, namely smooth aphasia and non-fluent aphasia. The divergent semantic method is used to provide a stimulus to fluent aphasia patients. Receptive language is the human ability to understand and process symbols, especially spoken language, while expressive language is the ability to produce meaningful words. Purpose: To determine the effectiveness of the divergent semantic method on expressive language skills in fluent aphasia sufferers in Jebres Districts. Method: This study used an experimental design, with pre-test and post- test designs. Data were analyzed using univariate and bivariate analysis. Test the hypothesis using Mc Analysis Test. Nemar. Research Result: This study obtained a p-value of 0,000, which means that this value is less than α = 0,05, so it can be interpreted that the divergent semantic method is effective in improving expressive language skills in fluent aphasia sufferers. Conclusion: There is effectiveness of the divergent semantic method on expressive language skills in fluent aphasia sufferers in Jebres Districts. Keywords: Effectiveness, Expressive Language, Fluent Aphasia, Divergent Semantic Methods.